The TNFA -857C/T Polymorphism: Association with Rheumatoid Arthritis and Anti-CCP Levels in a Mexican Population. (9th October 2019) - Agraz-Cibrián, Juan Manuel; Espinoza-De León, Gabriela Nohemí; Durán-Avelar, Ma. de Jesús; Vibanco-Pérez, Norberto; Ortiz-Martínez, Liliana; Vázquez-Reyes, Alejandro; Gutiérrez-Franco, Jorge; Ayón-Pérez, Miriam Fabiola; Zambrano-Zaragoza, José Francisco
Abstract : Rheumatoid arthritis (RA) is a chronic inflammatory disease whose association with SNPs has led to the identification of biomarkers in different populations. To determine the association of the -857C/T SNP of the TNFA gene with RA and clinical parameters, 233 RA patients and 237 healthy controls were included in this study. The -857C/T polymorphism was determined using the TaqMan® system and clinical features were also determined. We found that the -857C/T SNP was in Hardy-Weinberg equilibrium. Our results showed no association of the -857C/T SNP with RA; however, RA patients carrying the TT genotype showed lower anti-CCP levels than other groups. Therefore, the TT genotype could be a risk factor for developing anti-CCP-negative RA. Our results suggest that the T allele of the TNFA -857C/T SNP exerts an influence on anti-CCP levels and could be a candidate marker for anti-CCP-negative RA.